Targeted AAV5-Smad7 gene therapy inhibits corneal scarring in vivo. - Suneel Gupta; Jason T Rodier; Ajay Sharma; Elizabeth A Giuliano; Prashant R Sinha; Nathan P Hesemann; Arkasubhra Ghosh; Rajiv R Mohan (PLoS ONE, 2017)
Corneal scarring is due to aberrant activity of the transforming growth factor β (TGFβ) signaling pathway following traumatic, mechanical, infectious, or surgical injury. Altered TGFβ signaling cascade leads to downstream Smad (Suppressor of mothers against decapentaplegic) protein-mediated signaling events that regulate expression of extracellular matrix and myogenic proteins. These events lead to transdifferentiation of keratocytes into myofibroblasts through fibroblasts and often results in permanent corneal scarring. Hence, therapeutic targets that reduce transdifferentiation of fibroblasts into myofibroblasts may provide a clinically relevant approach to treat corneal fibrosis and improve long-term visual outcomes. Smad7 protein regulates the functional effects of TGFβ signaling during corneal wound healing. We tested that targeted delivery of Smad7 using recombinant adeno-associated virus serotype 5 (AAV5-Smad7) delivered to the corneal stroma can inhibit corneal haze post photorefractive keratectomy (PRK) in vivo in a rabbit corneal injury model. We demonstrate that a single topical application of AAV5-Smad7 in rabbit cornea post-PRK led to a significant decrease in corneal haze and corneal fibrosis. Further, histopathology revealed lack of immune cell infiltration following AAV5-Smad7 gene transfer into the corneal stroma. Our data demonstrates that AAV5-Smad7 gene therapy is relatively safe with significant potential for the treatment of corneal disease currently resulting in fibrosis and impaired vision.